The Influence Of Brain Vitalization Gymnastic Towards Short Term Memory Among The Children 8-12 Years Old - Prabaningtyas, Ayu Rizki; , Totok Budi Santoso , S.Fis , MPH; , Wahyuni, SSt.FT.M.Kes (2016)
Background : short term memory has got important role in conscious mind. If in conscious condition we solve problem. We often use this short term memory as a storage of problems and information taken from the long therm memory which are relevant with the problem. The children 8-12 years old have got the strong memory about everything. The like studying to remind everything. They are in the period of learning. In this learning period children is adding knowledge, skills and to accustom good habits. Objectives : this research is aimed to comprehend the influence of brain vitalization gymnastic towards short term memory among children 8-12 years old. Research menthod : this research is held with quantitative method with quasi experimental design pre and post with contor group design. The opulation in this research is the students of sd n plesan 1 and sd n nguter 2, the number of population is 100 students with 50 students of group treatments and 50 students of group control. Results : the result of wilcoxon test shows < 0,005 where the group treatment has got significant score of short term memory 0,000 showing there is a positive effect of short term memory pre and post toward the short term memory. Keywords : brain vitalization gymnastic, short term memory, children 8-12 years old.